STRATEGI GURU BIMBINGAN DAN KONSELING DALAM MENERAPKAN KEBERSIHAN LINGKUNGAN SEKOLAH DI SMPN 8 BANDA ACEH - Taslima, Taslima (UIN Sunan Kalijaga Yogyakarta, 2018)
The purposes of this study were to know teachers’ strategy in promoting the school environment sanitation and to identify the shortcomings arised when attempts to do so. The analysis method used were descriptive qualitative, and data collection techniques were observation, interview, documentation, and literature study. Furthermore, the objects of this research were 1 principal, counseling teachers, and students of SMPN 8 Banda Aceh. The result revealed teacher’s strategy in promoting the school environment sanitation were through group guiding, group counseling, orientation services, and information services. The shortcomings arose in new academic year when new students were recruited. These freshmen had to adapt to school policies, including on school environment sanitation. These adaptation process surely would take times.Keywords: counseling guidance teacher, cleanliness, school environment.